Nutritional and therapeutic properties of fenugreek (Trigonella foenum-graecum): a review. Issue 1 (1st January 2020) - Syed, Qamar Abbas; Rashid, Zainab; Ahmad, Muhammad Haseeb; Shukat, Rizwan; Ishaq, Anum; Muhammad, Niaz; Rahman, Hafiz Ubaid Ur
ABSTRACT: Current lifestyle, eating habits, stress, environmental factors and intensive use of synthetic chemicals in food processing and agriculture have radically increased the progression of several human diseases. Globally, researchers have been looking for natural therapeutic substances that can be used to treat or delay the onset of these lifestyle-related disorders. Numerous types of medicinal plants have shown the potential to be frequently used in the therapeutics due to the presence of several bioactive compounds. Among these, fenugreek is an important herb which has been recognized as an imperative medicinal plant by various scientists around the world. This herb has been widely reported as beneficial against numerous diseases such as cancer, hypercholesterolemia, diabetes and inflammation. Due to its medicinal value, the extracts/powders from different parts of fenugreek have been effectively utilized in food and pharmaceutical industries. Accordingly, the present review is an attempt to highlight the important nutritional benefits and curative applications of fenugreek as an effectual therapeutic agent against different diseases.